2006
DOI: 10.1525/mp.2006.24.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Singing in Aphasia

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 46 publications
1
16
1
Order By: Relevance
“…In transversal studies, the rhythmic component of intoned-speech production appears to be responsible for on-line facilitation of patients’ speech accuracy (Laughlin et al, 1979; Boucher et al, 2001; Stahl et al, 2011). Longitudinal studies have used variations of MIT where only a limited set of sentences (10 to 15) is repeatedly trained (i.e., palliative variations of MIT, see Zumbansen et al, 2014) and examined if participants improved their speech accuracy in normally spoken sentences trained either with intoned speech (i.e., with rhythm and pitch), with rhythmic speech (i.e., without musical pitch) or non-trained (Wilson et al, 2006; Stahl et al, 2013). Significant improvement was obtained for trained sentences compared to non-trained items and pitch did not add any beneficial effect over rhythm on speech accuracy immediately post-treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In transversal studies, the rhythmic component of intoned-speech production appears to be responsible for on-line facilitation of patients’ speech accuracy (Laughlin et al, 1979; Boucher et al, 2001; Stahl et al, 2011). Longitudinal studies have used variations of MIT where only a limited set of sentences (10 to 15) is repeatedly trained (i.e., palliative variations of MIT, see Zumbansen et al, 2014) and examined if participants improved their speech accuracy in normally spoken sentences trained either with intoned speech (i.e., with rhythm and pitch), with rhythmic speech (i.e., without musical pitch) or non-trained (Wilson et al, 2006; Stahl et al, 2013). Significant improvement was obtained for trained sentences compared to non-trained items and pitch did not add any beneficial effect over rhythm on speech accuracy immediately post-treatment.…”
Section: Introductionmentioning
confidence: 99%
“…When considered in conjunction with putative neuroplasticity mechanisms, this raises a number of hypotheses, including (1) that MIT would be more effective in individuals with previous singing experience who have already developed a specialized singing network or (2) that through regular singing practice, MIT could promote the development of a more “expert” singing network that would occupy left-hemisphere perilesional regions. The first hypothesis is indirectly supported in the existing literature, given that Wilson et al (2006) found that MIT was more effective than rhythmic speech in their case study of a trained musician, while Stahl et al (2013) did not find an advantage of singing over rhythmic speech in a group of non-musicians. Additional studies are needed to disentangle the relationship between music and language in aphasia and in MIT relative to expertise.…”
Section: Shared or Specific Features Of Music And Languagementioning
confidence: 84%
“…If observation, imitation, and synchronization of singing or intoned speech are interacting with a neural perception–action integration system, they might be expected to impact motor aspects of speech most strongly (Fadiga et al, 2002; Wilson et al, 2004). Indeed, some of the benefits of MIT are perhaps attributable to improvements in speech articulation (Sparks and Holland, 1976; Wilson et al, 2006) that subsequently lead to improvements in language output. Racette et al (2006) compared word production and intelligibility in individuals with aphasia when singing and speaking both alone and with an auditory model.…”
Section: Observation Imitation Integration and The Mirror Neuron Smentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Belin et al (1996) used positive emission tomography (PET) to demonstrate that MIT reactivates Broca's area in the left hemisphere in nonfluent aphasics. In yet another study, Wilson, Parsons and Reutens (2006) found that MIT was also effective for a patient with severe Broca's aphasia. The patient was a former musician with expressive aphasia.…”
Section: Poetry Therapy and Music Therapymentioning
confidence: 98%